Vulnerability assessment for the eastern African region to identify hotspots - Notenbaert, An Maria Omer; Kienberger, S.; Bett, Bernard K.; Hagenlocher, M.; Zeil, P.; Omolo, Abisalom (2012)
The output of this task identifies vulnerable sub-regions within the five country study area that can serve as the locus of higher resolution analysis and for testing adaptation strategies.